Visual-motor integration of younger school-aged children - Jelena Milić; Sladjana Djorem; Ana Lukić; Marko Petrović; Bojan Joksimović; Biljana Mijović; Radmila Balaban; Vesna Krstović Spremo; Dajana Žnogo ivanović; Veljko Marić (Биомедицинска истраживања, 2022)
Introduction: Visual-motor integration (VMI) is defined as the degree to which visual perception (VP) and finger-hand movements are well coordinated. The VMI consists of two components: VP and motor coordination (MC). The main goal of our research was to determine whether there are differences in age and gender categories in VMI, VP and MC scores, as well as whether there is a correlation between VMI and school success of younger school-aged children. Methods: Out of 103 student respondents, 52 were female (50.5%), aged 6 to 11 years (8.05 ± 1.44 years), divided into two groups according to age: 6-8 years (first, second and third grade) and 9-11 years (fourth to fifth grade). Data on the level of VMI were obtained by applying the following tests: Beery-Buktenica Developmental Test of VMI, VP test and MC test. Results: In the older age group of subjects, a significant difference was observed in the mean values of the score on the VMI (12.67 ± 1.92), VP (23.69 ± 3.21) and MC (24.34 ± 3.23) tests comparing to the younger group of subjects (9.98 ± 2.12; 20.80 ± 3.2; 19.65 ± 3.82) (p < 0.001), while the difference in the mean values of scores in relation to gender was not observed. A significant, positive and strong correlation was observed between the scores on the VMI, VP and MC test with the success of second to fifth grade students (p < 0.050). Conclusion: Given such a strong correlation between VMI and the success of younger students, we conclude that it is important that VMI disabilities are identified in time, so that these students can be referred for further assessment and receive the necessary support.
Keywords: younger school age; visual-motor integration; visual perception; motor coordination